Aquatisphaeria thailandica gen. et sp. nov. (Tetraplosphaeriaceae, Pleosporales) from freshwater habitat in Thailand - Li, Wen-Li; Bao, Dan-Feng; Liu, Ning-Guo; Hyde, Kevin D.; Liu, Jian-Kui (Phytotaxa, 2021)
A novel hyphomycetous genus collected from submerged wood in a freshwater stream in Thailand is introduced. The fungus is similar to Tetraplosphaeriaceae species in having subglobose conidial body and elongated setose appendages arising from conidial body. However, its unique combination of macronematous conidiophores and conidia composed with several columns of cells differs it from other genera in Tetraplosphaeriaceae. The phylogenetic analysis based on a combined LSU, ITS and SSU sequence data indicated that our two strains formed a distinct lineage in the family and they cannot be assigned to any existing genera. Therefore, we introduce a new genus Aquatisphaeria to accommodate the new taxa with A. thailandica as the type species. The detailed description, illustration and comparison with related taxa are provided.